Pengurusan kokurikulum dan hubungannya dengan tahap penglibatan pelajar dalam aktiviti kokurikulum - Kung, Teik Seng (2010)
Research and development in the area of co-curricular administrator at school level is important in order to improve the quality of education in Malaysia. This study aims to identify the level of co-curricular administration in terms of its planning, organizing, leading, and control administered, by the principal of the school. In addition, this study also aims to identify the relationship between the principal role as the administrator of co-curricular activities and the students' level of involvement in co-curricular activities in the schools of Perlis. The relationship of teacher as the adviser of co-curricular activities and The Policy Of Co-curricular Marks (10%) Of Admission to Universities and the students' level of participation in school co-curricular activities are also evaluated. This study employed a questionnaire to identify the co-curricular administration practiced in the school. A pilot study was conducted in order to ensure the reliability and validity of the questionnaires and was analysed through "Cronbach Alpha". The value was 0.926. The population of this study were 310 teachers from 11 secondary schools in Perlis. Data from the questionnaires was analysed through SPSS 12.0 (Statistical Package For The Social Sciences). In order to determine the relationship between the variables, Pearson Correlation test (r) was also conducted in order to illustrate the relationship between the independent variables with the dependent variable. Based on the respondents' perception, the study showed that the principal role in planning, operating and leading was working at a high level. However, the respondents' perception towards the controlling function held by the principal was at a moderate level. The study showed that there is a high relationship between the principal role as the administrator of co-curricular activities and the students' level of involvement in the co-curricular activities. In addition, the study also showed that there is high relationship between the teacher as the adviser of co-curricular activities and the students' level of involvement in the co-curricular activities. However, the relationship between The Policy Of Co-curricular Marks (10%) Of Admission to Universities and the students' level of involvement in the co-curricular activities was at a moderate level only